Front Cover: The Unexpected Helical Supramolecular Assembly of a Simple Achiral Acetamide Tecton Generates Selective Water Channels (Chem. Eur. J. 33/2022). Issue 33 (19th May 2022) - Dumitrescu, Dan G.; Rull‐Barull, Jordi; Martin, Anthony R.; Masquelez, Nathalie; Polentarutti, Maurizio; Heroux, Annie; Demitri, Nicola; Bais, Giorgio; Moraru, Ionut‐Tudor; Poteau, Romuald; Amblard, Muriel; Krajnc, Andraž; et al.
Abstract : Chiral channels with highly mobile water molecules result from the robust self‐organization of a simple achiral acetamide. Fully reversible release and re‐uptake of water molecules takes place near ambient conditions, with efficient water transport and a good selectivity against NaCl suggesting it to be an efficient candidate for desalination processes. More information can be found in the Research Article by A. van der Lee and co‐workers (DOI: 10.1002/chem.202200383 ).